Comparison of two alternate methods to establish an interrupted energy assessment rate - Ghajar, R. (1987)
Quantitative reliability evaluation is an important aspect of power system planning and operation. The indices produced in these applications are utilized in a wide range of management decisions throughout a utility. One issue which is often debated is the cost associated with a particular level of reliability. In order to make this argument complete, it is necessary to also thoroughly examine the worth or benefit associated with a particular level of reliability. Estimates of the impact of interruptions in service can be obtained by assessing the losses incurred by different customer types and classes. These data can then be used to generate a composite customer damage function for a given utility service area. In order to create a practical tool for assessing reliability worth, interruption costs must be related to the calculated indices used in system planning and operation. This paper uses two different approaches and a customer damage function to evaluate a factor designated as the Interrupted Energy Assessment Rate (IEAR) which can be used in conjunction with the calculated expected energy not supplied in the assessment of reliability worth.